Achieving market integration best execution, fragmentation and the free flow of capital - McCleskey, Scott (Securities Institute Operations Management S.)
Best execution, market integration, and other major financial market issues have traditionally been dealt with as separate matters requiring individual solutions. In Achieving Market Integration the author demonstrates the interrelated nature of these and other imperative problems, and sensibly reduces them to their common fundamental principles. Beginning with an in-depth examination of best execution in today's multiple-market environment, the book moves logically into an examination of market structure and the problems of achieving genuine integration. The book makes the case that order interaction is fundamental to addressing each of these issues, and develops a unified regulatory approach to achieve true market integration based on intermarket linkages and a cross-market best execution policy. This unique approach culminates in a coherent set of policy recommendations and an innovative framework for assessing the effectiveness of future policy proposals. *The first book on this important subject for the finance community *Explains the aims and proposes solutions to the difficulties of establishing a stock market that integrates the diverse national exchanges around Europe *Provides a discussion point for those lobbying the European Commission on formulating regulation for an integrated European capital market.